Detailed study on stiffness and load characteristics of film-riding groove types using design of experiments - Tibos, S. M.; Georgakis, C.; Harvey, K.; Amaral Teixeira, Joao (American Society of Mechanical Engineers (ASME), 2017)
In the application of film-riding sealing technology, there are various groove features that can be used to induce hydrodynamic lift. However, there is little guidance in selecting the relative parameter settings in order to maximize hydrodynamic load and fluid stiffness. In this study, two groove types are investigated—Rayleigh step and inclined groove. The study uses a design of experiments approach and a Reynolds equation solver to explore the design space. Key parameters have been identified that can be used to optimize a seal design. The results indicate that the relationship between parameters is not a simple linear relationship. It was also found that higher pressure drops hinder the hydrodynamic load and stiffness of the seal suggesting an advantage for using hydrostatic load support in such conditions.